2009
DOI: 10.1348/096317909x474786
|View full text |Cite
|
Sign up to set email alerts
|

Career transitions and their causes: A country‐comparative perspective

Abstract: This empirical paper investigates how individuals conceptualize causes of career transitions, focusing on the three European countries of Austria, Serbia, and Spain in comparison to the USA and China. Collectively, these countries represent four separate cultural regions according to Schwartz. Semi-structured interviews were conducted with members of three occupational groups: business people, nurses, and blue-collar workers. Analysis of the data generates greater insight about the existence of both region-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 56 publications
0
40
0
9
Order By: Relevance
“…We developed an initial template with which to code the timelines (see Table 1), based on a priori assumptions (derived from the literature) as to the themes that might emerge from our analysis (King, 2008). In considering what factors might influence appraisal we expected the following to be most influential: event type -whether it has an impact on identity (Barton et al, 2008;Thoits, 1991), and whether it is individually triggered or externally driven by others (Chudzikowski et al, 2009); the situational demands of the event -its familiarity, predictability, and clarity (Lazarus, 1999); and temporal factors -whether the event is occurring at a "good" or "bad" time (Lazarus, 1999). We coded each of the timelines, using the emoticons as a guide to positive/negative appraisal.…”
Section: Discussionmentioning
confidence: 99%
“…We developed an initial template with which to code the timelines (see Table 1), based on a priori assumptions (derived from the literature) as to the themes that might emerge from our analysis (King, 2008). In considering what factors might influence appraisal we expected the following to be most influential: event type -whether it has an impact on identity (Barton et al, 2008;Thoits, 1991), and whether it is individually triggered or externally driven by others (Chudzikowski et al, 2009); the situational demands of the event -its familiarity, predictability, and clarity (Lazarus, 1999); and temporal factors -whether the event is occurring at a "good" or "bad" time (Lazarus, 1999). We coded each of the timelines, using the emoticons as a guide to positive/negative appraisal.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Jorgenson (2000) found that women engineers in the United States actively hid family responsibilities to avoid perceptions that they lacked commitment to work, despite existing family friendly policies, a finding similar to a study of female British civil engineers (Franzway, Sharp, Mills, & Gill, 2009). Those carrying a disproportionate amount of family responsibility face conflicting career decisions, with variability in work patterns strongly influenced by gender (Chudzikowski et al, 2009). Work-life balance issues, lack of time spent with their children and feeling like an 'outsider' when these workers do return to their families were key negative outcomes found among a sample of FIFO workers in Queensland (Torkington, Larkins, & Gupta, 2011).…”
Section: The Australian Mining Industrymentioning
confidence: 99%
“…As personality plays a major role in career transitions (Chudzikowski, et al, 2009), it is only logical to assume that the personality-job-match plays an equally important role in pursuing new careers (Donahue, 2006). Therefore, individual differences in personality, attitude, ability, identity, self-concept and emotions plays a role in the choices the individuals make about their career (Peel & Inkson, 2008).…”
Section: Personality-job-matchmentioning
confidence: 99%
“…Culture seems to play a big role in career transition (Chudzikowski, et al, 2009;Gerber, Wittekind, Grote, Conway, & Guest, 2009). In fact, Schein (1984) stated that the specific viewpoint individuals have about their career depends on their culture.…”
Section: Cultural Impact On Career Transitionmentioning
confidence: 99%